Chronic Chagas Cardiomyopathy in the Brazilian Amazon region: clinical characteristics and regional distinctiveness - Elsa Isela Guevara Moctezuma; Elsa Isela Guevara Moctezuma; Susan Smith Doria; Susan Smith Doria; Jessica Vanina Ortiz; Jessica Vanina Ortiz; Débora Raysa Teixeira de Sousa; Débora Raysa Teixeira de Sousa; Victor Irungu Mwangi; Katia do Nascimento Couceiro; Katia do Nascimento Couceiro; Alba Regina Jorge Brandão; et al. (Frontiers Media S.A., 2023)
ObjectivesThis study aims to provide a comprehensive analysis of clinical and epidemiological data related to Chronic Chagas Cardiomyopathy (CCC) in the Amazon region of Brazil.MethodsA review of observational, retrospective, and cross-sectional studies related to Chagas Disease in the Amazon region of Brazil was conducted, and a case series addressing CCC in patients treated at the FMT-HVD outpatient clinic, a reference center for Chagas disease in Brazil, was carried out.ResultsClinical characteristics of 55 patients from the Amazon region with CCC were described. The most common electrocardiographic alteration observed was abnormal ventricular repolarization (AVR), present in 40% of cases. The most common echocardiographic finding was left ventricular systolic dysfunction (49%), followed by akinesia or hypokinesia of the inferior and/or inferolateral walls (38.1%) and the presence of an apical aneurysm (32.7%).ConclusionsOverall, this study demonstrates that CCC in the Amazon region presents clinical characteristics and severity that are similar to those observed in other regions. However, certain peculiarities, such as the frequency of right bundle branch block (RBBB) and anterior and septal involvement during the acute phase, require additional investigation to better comprehend the disease in the region. Overall, the study provides crucial clinical insights for the diagnosis and treatment of CCC in the Amazon region.